Venous thromboembolism and cancer - Gran, Olga Vikhammer (UiT The Arctic University of Norway, 2017)
The paper II of this thesis is not available in Munin. Paper II: Blix, K., Gran, O. V., Severinsen, M. T., Cannegieter, S., Jensvoll, H., Overvad, K., Hammerstrøm, J., Tjønneland, A., Næss, I. A., Brækkan, S. K., Rosendaal, F. R., Kristensen, S. R., Hansen, J. B.: «Impact of time since diagnosis and mortality rate on cancer-associated venous thromboembolism in a general population – the Scandinavian Thrombosis and Cancer (STAC) cohort». (Manuscript). Venous thromboembolism (VTE) is a collective term for deep vein thrombosis and pulmonary embolism. VTE is a common cause of mortality and morbidity in patients with cancer, and may also be the first sign of an underlying malignancy. The first aim of this thesis was to investigate the risk of incident and recurrent VTE in active cancer compared to a cancer-free reference population and to explore the influence of genetic risk factors on cancer-related VTE. Secondly, we aimed to investigate the association between plasma D-dimer levels at VTE and the subsequent risk of cancer. All four papers in this thesis utilize the Tromsø Study. The first survey of the Tromsø Study was conducted in 1974 and, thus far, seven surveys have been completed. Our study populations were recruited from the Tromsø 4 and 6 surveys for Paper I, and Tromsø 1 to 6 surveys for Papers III and IV. Participants were followed from 1994, when the VTE registry was established in Tromsø, throughout 2012. Paper II was based on the Scandinavian Thrombosis and Cancer (STAC) cohort, which comprises individual data from the Tromsø 4 survey, the second Nord-Trøndelag Health Study (HUNT2) and the Danish Diet, Cancer and Health (DCH) Study. Validated VTE events and cancer diagnoses were registered from inclusion (1993 to 1997) to the end of follow-up (2007 to 2012). We found a joint effect between two single nucleotide polymorphisms (SNPs) in the F5 gene (F5 rs6025 (Factor V Leiden) and F5 rs4524) and active cancer on the risk of VTE. The incidence of cancer-related VTE increased considerably in the six ...